Cholesteryl Ester Transfer Protein Inhibitory Activity of New 4-Bromophenethyl Benzamides - Abu Khalaf, Reema; NasrAllah, Areej; AlBadawi, Ghadeer (Jordan Journal of Pharmaceutical Sciences, 2023)
Cardiovascular diseases, as coronary heart disease, heart failure, and hypertension are the first leading cause of death in the United States and the third globally. CETP is a glycoprotein excreted mainly from the liver and found in plasma. Normal plasma CETP concentration is 1-4 µg/ml, while the ratio increased 70-80% in dyslipidemic patients. There is a growing need for new CETP inhibitors which encourages us to conduct this research. In this work, synthesis and in vitro study for four new 4-bromophenethylbenzamides 9a-d were carried out. In vitro study showed that the targeted compounds 9a-d exhibit acceptable activity against CETP, where compound 9a has a % inhibition of 40.7 at 10 µM concentration. It was found that the presence of the oxy group in both 9a and 9c enhances their activity which could be attributed to Hydrogen-bond formation with the amino acid residues of the CETP binding site.